An optimum bank fund allocation plan from a loan portfolio: the case study of Atwima Kwanwoma Rural Bank - Sebil, Charles (2011)
A thesis submitted to the Board of Postgraduate Studies, University of Science and Technology, Kumasi, Ghana, in partial fulfilment of the requirements for the Award of the degree of Master of Science (M.Sc) in Mathematics, 2005